How much inundation occurs in the Amazon River basin? - Fleischmann, Ayan Santos; Papa, Fabrice; Fassoni-Andrade, Alice; Melack, John M.; Wongchuig, Sly; Paiva, Rodrigo Cauduro Dias; Hamilton, Stephen K.; Fluet-Chouinard, Etienne; Barbedo, Rafael; Aires, Filipe; Al Bitar, Ahmad; Bonnet, Marie-Paule; et al. (Remote sensing of environment, 2022)
The Amazon River basin harbors some of the world's largest wetland complexes, which are of major importance for biodiversity, the water cycle and climate, and human activities. Accurate estimates of inundation extent and its variations across spatial and temporal scales are therefore fundamental to understand and manage the basin's resources. More than fifty inundation estimates have been generated for this region, yet major differences exist among the datasets, and a comprehensive assessment of them is lacking. Here we present an intercomparison of 29 inundation datasets for the Amazon basin, based on remote sensing only, hydrological modeling, or multi-source datasets, with 18 covering the lowland Amazon basin (elevation <500 m, which includes most Amazon wetlands), and 11 covering individual wetland complexes (subregional datasets). Spatial resolutions range from 12.5 m to 25 km, and temporal resolution from static to monthly, spanning up to a few decades. Overall, 31% of the lowland basin is estimated as subject to inundation by at least one dataset. The long-term maximum inundated area across the lowland basin is estimated at 599,700 ± 81,800 km2 if considering the three higher quality SAR-based datasets, and 490,300 ± 204,800 km2 if considering all 18 datasets. However, even the highest resolution SAR-based dataset underestimates the maximum values for individual wetland complexes, suggesting a basin-scale underestimation of ~10%. The minimum inundation extent shows greater disagreements among datasets than the maximum extent: 139,300 ± 127,800 km2 for SAR-based ones and 112,392 ± 79,300 km2 for all datasets. Discrepancies arise from differences among sensors, time periods, dates of acquisition, spatial resolution, and data processing algorithms. The median total area subject to inundation in medium to large river floodplains (drainage area > 1000 km2) is 323,700 km2. The highest spatial agreement is observed for floodplains dominated by open water such as along the lower Amazon River, whereas intermediate agreement is found along major vegetated floodplains fringing larger rivers (e.g., Amazon mainstem floodplain). Especially large disagreements exist among estimates for interfluvial wetlands (Llanos de Moxos, Pacaya-Samiria, Negro, Roraima), where inundation tends to be shallower and more variable in time. Our data intercomparison helps identify the current major knowledge gaps regarding inundation mapping in the Amazon and their implications for multiple applications. In the context of forthcoming hydrology-oriented satellite missions, we make recommendations for future developments of inundation estimates in the Amazon and present a WebGIS application (https://amazon-inundation.herokuapp.com/) we developed to provide user-friendly visualization and data acquisition of current Amazon inundation datasets. •Intercomparison of 29 inundation datasets from remote sensing/hydrological modeling.•31% of the lowland Amazon basin is estimated as subject to inundation by at least one product.•Basin-wide, long-term maximum inundated areas is 599,700 ± 81,800 km2.•Highest spatial agreement is observed for floodplains dominated by open water.•Striking spatial disagreement exists among estimates for interfluvial wetlands.